Factores de riesgo para el desarrollo de fístula anorrectal - Luna Yangali, Hermes Eduardo (2016)
TITLE: “Risk factors for the development of anorectal fistula” OBJECTIVES: To determine whether male sex, early adulthood, overweight, diabetes mellitus and driver occupation are risk factors associated with the occurrence of anorectal fistula. METHODOLOGY: Analytical case-control study. MATERIAL AND METHODS: Population was conformed of patients diagnosed with anorectal fistula treated in the surgical service at the Belén Hospital of Trujillo in the period January 2010 to July 2016. We reviewed 168 medical records (56 cases and 112 controls), and then formed the database. To measure the association level we used Odss ratio (OR) and to verify its significance, the chi-square test. Once the risk factors were identified, the multivariate analysis of logistic regression identified the isolated behavior of each variable. RESULTS: Male gender (OR: 7,287, CI: 3,374-15,738, p<0,00) and early adulthood (OR: 2.41, CI: 1.039-5.587, p<0,04) were found as risk factors. The presence of overweight, Diabetes mellitus and driver occupation were not statistically significant (p> 0.05) and therefore were not associated with the development of anorectal fistula. CONCLUSIONS: Male gender and early adulthood are risk factors for the development of anorectal fistula. Overweight or obesity, Diabetes mellitus and driver occupation were not associated with the onset of this pathology